Preto contra branco . Black Against White - Morales, Wagner (Brazil, 2004)
Verzio FF submission In one of the southern suburbs of São Paulo, on the border between the favelas and the better neighbourhoods, is a soccer field where blacks and whites meet once a year to play against each other. A white and a black friend initiated the event thirty years ago, with fraternisation as their goal. The rest of the year, the match is food for stories, legends and jokes. The film looks at this community that it trying the get rid of the racial phantoms with more or less success.